Contact Performance and Thermal Stability Improvement of Amorphous InGaZnO Thin-Film Transistors by Using a Buffer/Cu/Buffer Source/Drain Electrode Structure. Issue 1 (March 2020) - Li, Gongtan; Zhu, Feng
Abstract: This paper discussed the contact characteristics and thermal stability of a-IGZO TFT with various kinds of buffer/Cu/buffer electrode structure. The work found that the a-IGZO TFTs with Cu electrode and Mo/Cu/Mo electrode show worse thermal stability than these with ITO/Cu/ITO electrode. The work speculates that the contact performance deterioration after post-anneal was due to Cu oxidation and an interface separation between Mo and Cu, respectively. The work used the G-function method to discuss the contact performance of a-IGZO TFTs with the different kinds of S/D electrodes. The a-IGZO TFT with an ITO/Cu/ITO electrode shows a smaller contact resistance than the other TFTs and had an ohmic contact between the a-IGZO and ITO. In terms of thermal stability and contact performance, ITO/Cu/ITO electrode is a better choice than Mo/Cu/Mo electrode.